Gas-liquid dispersion in micronozzles and microreactor design for high interfacial area. (21st September 2017) - Reichmann, Felix; Tollkötter, Alexander; Körner, Sarah; Kockmann, Norbert
Abstract: Gas-liquid flow is frequently investigated in microreactor research, but mainly focused on well-described Taylor-bubble flow. Dispersed flow featuring small bubbles results in increased specific surface-to-volume ratio and more stable flow in microchannels. The influence of local energy dissipation rate and channel geometry was investigated on gas-liquid dispersion in nozzles with hydraulic diameter from 0.25 to 0.5 mm. Resulting bubble diameter and its size distribution were examined. For systems with increased bubble coalescence, micronozzles can be switched in series to redisperse the flow for augmented mass transfer. The contribution will give a fundamental view on bubble generation, redispersion for dispersed gas-liquid systems in microstructured devices together with design and scale-up discussion. Highlights: Design of a flexible multiscale reactor system for reduced pressure loss Turbulent bubble breakup in micronozzles for enhanced interfacial area Investigation of turbulent and laminar breakup region and mechanisms Influence of pressure loss and energy dissipation rate on Sauter and mean diameter Localization of maximum local energy dissipation rate and bubble breakup point